2020
DOI: 10.32553/ijmsdr.v4i8.657
|View full text |Cite
|
Sign up to set email alerts
|

Clinicohistopathological Profile of Nasal and Sinonasal Lesions: A Study From Central India

Abstract: Background: Nasal and sinonasal lesions comprise common as well as rarest rare lesions. This region being a site of histopathologically diverse lesions, interests pathologists. Objectives: The study aimed to find out incidence of nasal and sinonasal lesion with frequency of non-neoplastic, neoplastic  lesions,  to study spectrum of lesions histopathologically along with correlation of clinical and radiology findings. Material and methods: It was a 2 year retrospective observational study involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Parallel to our results, Pushpalatha et al, [7] demonstrated that 55 out of 85 nasal polyps were allergic type (68.75%). Other studies showed variable results, Jaison et al, [8] and Khade et al, [9] found that nonallergic type was 28 out of 50 (56%) and 33 out of 41 (80.4%), respectively.…”
Section: F E Gmentioning
confidence: 91%
See 1 more Smart Citation
“…Parallel to our results, Pushpalatha et al, [7] demonstrated that 55 out of 85 nasal polyps were allergic type (68.75%). Other studies showed variable results, Jaison et al, [8] and Khade et al, [9] found that nonallergic type was 28 out of 50 (56%) and 33 out of 41 (80.4%), respectively.…”
Section: F E Gmentioning
confidence: 91%
“…As regarding the relation between younger age categories and nasal polyps, it was significant (p=0.042). Also, Khade et al, [9], reported 38.3% of 41 patients of nasal polyps belonged to 20-50 age group. However, We et al, [14] found that increasing trend of nasal polyps prevalence with increasing age was statistically significant (p-value> 0.001).…”
Section: F E Gmentioning
confidence: 95%